PENGEMBANGAN MODEL EVALUASI AFEKTIF MATA PELAJARAN AKIDAH AKHLAK DI MTs MUHAMMADIYAH PURBOLINGGO LAMPUNG TIMUR - shaine arsianti; Cahaya Khaeroni; Iswati (Universitas Muhammadiyah Metro, 2026)
The problem with this research is that there is no affective evaluation in the subject of moral beliefs. One of the curricula that is still being implemented at MTs Muhammadiyah Purbolinggo East Lampung is the 2013 Curriculum which includes assessment of the affective (attitude), cognitive (knowledge) and psychomotor (skills) domains. However, in its implementation at MTs Muhammadiyah Purbolinggo, East Lampung, there is no special assessment for the affective domain in the Aqidah Akhlak subject. Therefore, the research seeks to examine the development of the Affective Evaluation Model for Aqidah Moral Subjects at MTs Muhammadiyah Purbolinggo, East Lampung. This research aims to find out how to develop an affective evaluation model for the Aqidah Akhlak subject and to determine the effectiveness of the affective evaluation model for the Aqidah Akhlak subject at MTs Muhammadiyah Purbolinggo, East Lampung. The research method used is the Brog and Gall R&D development method. The research subjects were students of class VIII C MTs Muhammadiyah Purbolinggo East Lampung. The data collection techniques used were observation, interviews, questionnaires and documentation. The data analysis used was a media validation questionnaire and a respondent questionnaire which was measured using a Likert scale with a score range of 1-5. Based on the research results, it shows that the development of an affective evaluation model for the Aqidah Akhlak subject at MTs Muhammadiyah Purbolinggo, East Lampung in the form of an affective evaluation pocket book is effective and interesting with a very attractive feasibility scale if the model response level in affective evaluation in large and small groups reaches 81%-100 %, attractive reaches 61%-80%, quite attractive reaches 41%-60%, less attractive reaches 21%-40%, and very unattractive reaches 0%-20%. The feasibility of the affective evaluation model in the Aqidah Akhlak subject obtained results from the material validator with a percentage of 73% and the design validator with a percentage of 80%, so the affective evaluation model developed by the researcher is declared